Information and anti-terrorist security of Poland. A critical analysis exemplified with the tasks and activity of the Internal Security Agency - Rosicki, Remigiusz (Instytut Nauk Politycznych Uniwersytetu Warszawskiego, 2015)
The subject matter of the analysis conducted in the text is information and anti-terrorist security of Poland, which has been presented within the context of a clash between two spheres – the state and the private sphere. Furthermore, the issues of security have been supplemented with a description of the tasks and activity of the Internal Security Agency, as well as a synthetic appraisal of a terrorist threat to Poland. The main parts of this work are concerned with: (1) the state and the private sphere, (2) " terrorism " and terrorist offences, (3) the tasks and activity of the Internal Security Agency, (4) an appraisal of a terrorist threat to Poland. Given the necessity to elaborate the research problem, the text features the following research questions: (1) To what extent does referring to a threat to security influence a limitation on rights and freedoms in Poland (with regard to the clash between the state and the private sphere)?, (2) To what extent do the tasks and activity of the Internal Security Agency influence the effectiveness of anti-terrorist security in Poland?
Keywords: information security; bezpieczeństwo informacji; anti-terrorism security; bezpieczeństwo antyterrorystyczne; Internal Security Agency; Agencja Bezpieczeństwa Wewnętrznego; counterespionage; kontrwywiad; terrorist offenses; przestępstwa terrorystyczne; legal modalities; modalności prawne